THE EXISTENCE OF IN ABSENTIA TRIALS IN CORRUPTION CASES FROM THE PERSPECTIVE OF JUSTICE - Hendri, (Proceeding International Conference on Social Sciences, 2026)
Law Number 8 of 1981, also known as the Criminal Procedure Code (KUHAP), regulates the procedures for resolving cases through trials in court, either with the presence of the defendant or without his presence (In Absentia). In this regard, the author is interested in writing and conducting research on the procedure for resolving cases through the In Absentia trial mechanism. According to the provisions of criminal procedure law, the settlement of a case should involve the presence of the defendant. However, In Absentia trials, especially for extraordinary crimes such as corruption, can still be conducted in court even without the presence of the defendant. In this research, the problem formulation includes 1) How is the existence of In Absentia trials in the Indonesian Criminal Procedure Law system? 2) How can state financial losses be recovered using the In Absentia trial instrument? This type of research is normative legal research. Normative legal research emphasizes law as a norm (rule), so the research focuses on positive law. Articles 196 and 214 of the Criminal Procedure Code explicitly contain limited provisions regarding the defendant's absence from trial proceedings. However, these articles allow for in-absentia trials in special or urgent circumstances. One of the primary and most important goals in eradicating corruption is asset recovery. In absentia decisions allow judges to impose additional penalties in the form of restitution and confiscation of the convict's assets, which is the most practical objective of the mechanism.